ROLE OF SAFETY LEADERSHIP, K3 EXPERT COMMITMENT, ACCOUNTABILITY ON JOB SATISFACTION, AND SAFETY PERFORMANCE - Sumarsid Sumarsid; Heri Purwanto; Kurniawansyah Kurniawansyah (Jurnal Ekonomi, 2022)
Variable rates of workplace accidents can partly contribute to inefficient cooperation and communication patterns among workers. Therefore, the researchers set out to find out how job satisfaction and safety performance are related to factors like safety leadership, the dedication of OSH experts, and responsibility for accidents. For this study, we used the descriptive quantitative research method, and for data analysis, we employed the partial most minor square testing with model fitting. In addition, they are using a questionnaire to collect responses from 99 employees as part of the data collection process. According to the study's findings, safety leadership, as well as the commitment and accountability of K3 experts, significantly impact job satisfaction. In addition, the study discovered that factors such as job satisfaction and safety leadership affect safety performance. Meanwhile, K3 expert commitment and accountability only significantly affect company performance. According to the study's findings, workers report higher levels of job satisfaction when leadership, safety, K3 expert commitment, and accountability effectively implement. It suggests that employees' higher levels of job satisfaction will affect the organisation's ability to improve its safety performance. However, the research found that incidents where K3 expert commitment and accountability didn't found, which were able to improve safety performance. The condition arises as a result of a lack of commitment part of employees to implementing K3 and accountability. The implication is that it is necessary to position K3 aspects so that they cannot separate from one another as an integral part of the company's operations and the consequences for improving safety performance standards